Sexuality in later life: sexual desire and satisfaction among Malay older persons in Malaysia - Minhat, Halimatus Sakdiah; Mat Din, Hazwan; Ibrahim, Rahimah; Nor Akahbar, Siti Aisyah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Malaysia is known for its shy and prudent community that indirectly causing the stigma and taboos related to later life sexuality. This study aimed to explore the sexual desire and satisfaction in later life among the Malay ethnic elderly in Malaysia who were living in the urban area, where discussions about sexual issues are perceived less sensitive and stigmatized. Methods: A total of 234 eligible elderly were approached but only 160 older people completed the questionnaire, sampled using multistage cluster sampling method. Face-to-face interviews were conducted using questionnaires consisted of sociodemographic characteristics, cognitive function, perceived health status, presence of chronic illnesses, smoking history, disability, perceived sexual problems, sexual desire and satisfaction. Multiple logistic regression was conducted to determine the associated factors for sexual desire and satisfaction, respectively. All tests significant level was set at 0.05. Results: Majority of the respondents were having sexual desire (53.8%) and not satisfied with their sexual life (51.3%), with elderly women (55.7%) experienced more sexual problems compared to men. The results showed male, being married, good perceived health and absence of arthritis were the significant contributing factors of better sexual desire. Having good health perception, being married and absence of sexual problems were significantly predicting better sexual satisfaction. Conclusion: The study emphasized the multifactorial aspects contributed towards the sexual dissatisfaction among the respondents despite having desire for sexual activity. Focus should be given to elderly women who tend to have multiple chronic diseases and more likely a widow due to their longer life expectancy.